0.85 THz truncated sine waveguide traveling‐wave tube with sheet beam tunnel. Issue 14 (13th June 2018) - Fang, Shuanzhu; Xu, Jin; Jang, Xuebin; Lei, Xia; Ding, Chong; Li, Qian; Wu, Gangxiong; Yang, Ruichao; Zhang, Luqi; Huang, Minzhi; Tang, Tao; Zhao, Guoqing; et al.
Abstract : A sine waveguide (SWG) traveling‐wave tube with sheet electron beam tunnel is proposed to amplify the high‐frequency terahertz wave. In this study, the slow wave characteristics including the dispersion properties and interaction impedances have been investigated by using the eigenmode solver in the 3D electromagnetic simulation software Ansoft HFSS. The truncated SWG slow wave structure possesses the relatively large average coupling impedance. The beam–wave interaction characteristics of truncated SWG with sheet electron beam tunnel are calculated by high‐frequency simulation software CST. From the particle‐in‐cell simulation results, this beam–wave interaction circuit can produce >490 mW ranging from 0.845 to 0.855 THz with a corresponding gain over 22 dB.